Optimal design of automobile exhaust system using GT-power - Mohiuddin, A. K. M.; Rahman, Mohammed Ataur; Mohd Subri, Mohd Dzaidin (Department of Mechanical Engineering, University of Malaya, 2007, 2007)
The exhaust system consists of the exhaust manifold, the header, the catalytic converter, the muffler, and the tailpipe. Certain flow characteristics must be met for the optimal performance of the exhaust system. The main objective of this paper is to design exhaust system (particularly the exhaust manifold) using GT-Power software and to compare its performance with an existing system. The newly designed exhaust manifold shows lower back pressure which ultimately results better performance of the engine.